2022
DOI: 10.3390/polym14204370
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Water-Soluble Chitosan on the Inhibition of Crystal Nucleation of Alpha-Mangostin from Supersaturated Solutions

Abstract: The use of an amorphous drugs system to generate supersaturated solutions is generally developed to improve the solubility and dissolution of poorly soluble drugs. This is because the drug in the supersaturation system has a high energy state with a tendency to precipitate. In the amorphous solid dispersion (ASD) formulation, it was discovered that polymer plays a critical role in inhibiting nucleation or crystal growth of the drugs. Therefore, this study aimed to evaluate the crystallization inhibition of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…The interactions between organic additive molecules and solutes include hydrogen bonding, hydrophobic interaction, π–π stacking, and other chemical forces. Budiman et al ’s study on maintaining alpha-mangostin (AM) , found that hydrocarbyl groups of water-soluble chitosan molecules and methyl groups of PVP molecules could form hydrogen bonds with the carbonyl group of AM through Fourier transform infrared (FT-IR), NMR, and computer studies, thereby inhibiting the molecular mobility of alpha-mangostin and inhibiting the formation of crystal nuclei. Liu et al found that the hydrophobic interaction between cyclodextrin and two drugs with low water solubility, namely carvedilol and chlorthalidone, could effectively inhibit the crystallization of the two drug molecules, and the ability of cyclodextrin to inhibit crystallization was closely related to its hydrophobicity.…”
Section: Methodologies and Strategies For Crystallization Inhibitionmentioning
confidence: 99%
“…The interactions between organic additive molecules and solutes include hydrogen bonding, hydrophobic interaction, π–π stacking, and other chemical forces. Budiman et al ’s study on maintaining alpha-mangostin (AM) , found that hydrocarbyl groups of water-soluble chitosan molecules and methyl groups of PVP molecules could form hydrogen bonds with the carbonyl group of AM through Fourier transform infrared (FT-IR), NMR, and computer studies, thereby inhibiting the molecular mobility of alpha-mangostin and inhibiting the formation of crystal nuclei. Liu et al found that the hydrophobic interaction between cyclodextrin and two drugs with low water solubility, namely carvedilol and chlorthalidone, could effectively inhibit the crystallization of the two drug molecules, and the ability of cyclodextrin to inhibit crystallization was closely related to its hydrophobicity.…”
Section: Methodologies and Strategies For Crystallization Inhibitionmentioning
confidence: 99%
“…This suggests that the physical interactions between the PVA and Biobran in the core effectively slowed down the Biobran release from the nanobrous scaffolds. [98][99][100] Notably, despite the higher hydrophilicity of B30 than B10 and B20, its Biobran release rate is comparatively slower. This can be attributed to its high crystallinity, small ber diameter, and pore size, which also contributed to its enhanced stability during degradation.…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…In comparison with the fusion method, SDs prepared via solvent evaporation often show evidence of intermolecular interactions, which could explain the absence of the "parachute" effect during dissolution studies. Intermolecular interactions can suppress molecular mobility, thereby inhibiting the formation of the crystal nucleus and recrystallisation [48]. Nevertheless, several challenges were reported, including the limited solubility of sugars in organic solvents and the necessity of removing organic solvents to avoid solvation during storage.…”
Section: Solid Dispersions Of Sugar Carriersmentioning
confidence: 99%